Patterning of children's sedentary time at and away from school - Abbott, R.; Straker, Leon; Mathiassen, S. (Nature Publishing Group, 2013)
Objective: Sedentary behavior in children is positively associated with an increased risk of both obesity and insulin resistance. Children spend a considerable portion of their awake time in sedentary behavior; however, the pattern of accumulation is not known. Thus the objective of this study was to describe the patterning of sedentary behavior of children at and away from school. Design and Methods: The patterns of sedentary time in a sample of 53 children (28 girls) aged 10-12 years during school-term time were examined. Children wore an accelerometer for 1 week. Total sedentary time, prolonged sequences (bouts) of sedentary time, and frequency of active interruptions to sedentary were examined on school days and weekends and within school time and non-school time on school days.Results: The data did not support our hypothesis that children accumulated more sedentary time on school days when compared with weekend days (mean [SD]: 64.4% [5.3] vs. 64.9% [9.0], P = 0.686). However, when comparing school time with non-school time on school days, children accumulated more sedentary time at school (66.8% [7.3] vs. 62.4% [5.2], P < 0.001) and spent more time at school in sustained sedentary sequences, that is, uninterrupted sedentary time for 30 min or more (75.6 min [45.8] vs. 45.0 min [26.8], P < 0.002). The children also recorded less breaks per sedentary hour within school time when compared with non-school time (8.9 h−1 vs. 10.2 h−1, P < 0.001). Conclusion: Reducing total sedentary time spent both in and out of school remains an important challenge. Interrupting sedentary time more often in the “working” (school) day could also reap important musculoskeletal and metabolic health rewards for children.